(untitled) (Medical Forum Monthly, 2022)
Objective: To compare CVC tip cultures with CVC blood cultures versus CVC blood cultures alone in identification of organisms in patients with sepsis admitted in Intensive Care Unit. Study Design: Retrospective Cohort study Place and Duration of Study: This study was conducted at the Medical Intensive Care Unit of Aga Khan University Hospital, Karachi from Jan, 2021 to Dec, 2021. Materials and Methods: Severe septic patients >18 years of age admitted in ICU with CVC inserted and atleast one CVC blood culture sent, were included and patients with previously known culture/organism on ICU arrival were excluded. SPSS v25.0 was used for data analysis. Frequency and percentages were reported for qualitative data while mean and standard deviation was reported for quantitative data. Results: Total 139 patients were included in the study with mean age of 53.45 ± 16.17 years with mean duration of CVC was 5.76 ± 2.89 days. Most common source of sepsis was respiratory system with 57(41%) of cases.%). 73(52.5%) patients had improved and the mortality was around 66(47.5%). 49(35.3%) patients CVC tip cultures were sent along with CVC blood cultures from which 49 CVC tip 27(55%) were positive for organism growth while 22 (45%) were negative and 11(22%) patients had CVC blood cultures positive. In 90 patients only CVC blood cultures were sent, 28(31%) were positive for any organism growth. Most common organism in our study was Acinetobacter. Conclusion: CVC tip cultures were effective predictors for identification of organisms in septic patients when combined with CVC blood cultures rather than using CVC blood cultures alone